The perio-esthetic-restorative approach for anterior rehabilitation - Nitin Tomar; Tushika Bansal; Marisha Bhandari; Anamika Sharma (Wolters Kluwer Medknow Publications, 2013)
Ensuring clinical success begins with a careful discussion of treatment planning, comprehensively covering all variables in simple to complex cases. Procedures including the crown lengthening surgery, furcation treatment and mucogingival therapy and tooth restoration are essential treatment regimens requiring multifaceted expertise. The interplay of periodontics and restorative dentistry is present at many fronts including the response of the gingival tissue to the restorative preparations. Dental restorations and periodontal health are inseparably interrelated. The adaptation of the margins, the contours of the restoration, the proximal relationships and the surface smoothness have a critical biological impact on the gingiva and the supporting periodontal tissues. The different surgical procedures used for crown lengthening are gingivectomy/gingivoplasty, apically positioned flap with or without osseous resection and orthodontic extrusion. The paper presents crown lengthening of severely mutilated teeth to increase the clinical crown height for adequate restoration.